2010
DOI: 10.1021/jf103310g
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Flavonoid Biosynthesis Genes and Accumulation of Phenolic Compounds in Common Buckwheat (Fagopyrum esculentum)

Abstract: Common buckwheat (Fagopyrum esculentum) is a short-season grain crop that is a source of rutin and other phenolic compounds. In this study, we isolated the cDNAs of 11 F. esculentum enzymes in the flavonoid biosynthesis pathway, namely, phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate:CoA ligase (4CL) 1 and 2, chalcone synthase (CHS), chalcone isomerase (CHI), flavone 3-hydroxylase (F3H), flavonoid 3'-hydroxylase (F3'H), flavonol synthase (FLS) 1 and 2, and anthocyanidin synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 27 publications
10
106
0
Order By: Relevance
“…List of fragment ions generated in the mass spectrum and tandem mass spectrum related to the peptide identification from the tryptic digests of ReCHS1 and ReCHS2 proteins Table S2). A similar trend for rutin accumulation was reported in F. esculentum, which has been well studied for rutin and its biosynthetic machinery (Li et al, 2010).…”
Section: Expression Pattern Of Rechs Genes and Flavonoid Accumulationsupporting
confidence: 53%
“…List of fragment ions generated in the mass spectrum and tandem mass spectrum related to the peptide identification from the tryptic digests of ReCHS1 and ReCHS2 proteins Table S2). A similar trend for rutin accumulation was reported in F. esculentum, which has been well studied for rutin and its biosynthetic machinery (Li et al, 2010).…”
Section: Expression Pattern Of Rechs Genes and Flavonoid Accumulationsupporting
confidence: 53%
“…This polyphenolic compound has strong antioxidant activity which was confirmed in in vivo studies [27][28][29]. Li et al [30], who studied the ethanolic extract, have reported that leaves of common buckwheat contained 2.07/100 mg DW of ferulic acid. According to the best knowledge of authors there was no information concerning the identification of ferulic acid as well as sinapinic acid and p-coumaric acid in infusions prepared from the buckwheat leaves.…”
Section: Discussionmentioning
confidence: 76%
“…Li et al [30] showed that leaves of buckwheat contained rutin, but they did not identified quercetin. Also Zieli艅ska et al [31] reported that leaves of common and tartary buckwheat were a good source of rutin.…”
Section: Discussionmentioning
confidence: 99%
“…In the mother-fern culture during summer to autumn harvest, by improved the light environment rutin content become significantly high (Maeda et al, 2010). Study in buckwheat showed that rutin getting higher according to the light such as UV-B specifically (Lee et al, 2001;Kreft et al, 2002;Li et al, 2010;. The trial in arabidopsis (Arabidopsis thaliana) also shows that flavonoids biosynthetic genes were effectively express by the induction of UV-B light and blue light, though none in dark condition (Kubasek et al, 1992;Fuglevand et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, unlike others plant such as, buckwheat, and arabidopsis, the enzymes involved in flavonoids biosynthesis pathways on asparagus have not been identified yet (Kubasek et al, 1992;Li et al, 2010;. Particular studies about mechanism of the rutin increase by supplemental lighting in asparagus from molecular biology aspect are needed.…”
Section: Discussionmentioning
confidence: 99%